Group harmony : the Black urban roots of rhythm & blues - Goosman, Stuart L., 1953-2017 (University of Pennsylvania Press, 2005)
Drawing on dozens of interviews with performers, deejays, and industry professionals, Group Harmony details the emergence of vocal rhythm & blues out of black urban neighborhoods in the postwar period.